Photonics-based distributed radar - Leitão, Lucas Sabença (2021)
The Radar technology has been presented as a promising solution to the demanding challenges of the modern society, mainly due to its exibility and non-invasiveness, making it suitable for a wide range of useful applications. This dissertation addresses the development and testing of a distributed Radar system with a central processor and radio-over- bre signal transport. In this scope, besides analysing di erent waveforms suitable to be implemented (namely, OFDM and FMCW), a simulator capable of evaluate the relationship between a system con guration/parametrization and its performance was also developed. Additionally, the whole system was engineered, including some modules already developed in the scope of the RETIOT project and others developed, tested and analysed within the scope of this work. Finally, some preliminary testing was made, including the system behavior estimation.